Assembling diuranium complexes in different states of charge with a bridging redox-active ligand. Issue 38 (7th September 2022) - Modder, Dieuwertje K.; Batov, Mikhail S.; Rajeshkumar, Thayalan; Sienkiewicz, Andrzej; Zivkovic, Ivica; Scopelliti, Rosario; Maron, Laurent; Mazzanti, Marinella
Abstract : Convenient routes to dinuclear complexes of uranium where two uranium centers are bridged by the redox-active ligand bpym were identified resulting in unique and stable radical-bridged dimetallic complexes of U(iii ) and U(iv ) showing SMM behaviour. Abstract : Radical-bridged diuranium complexes are desirable for their potential high exchange coupling and single molecule magnet (SMM) behavior, but remain rare. Here we report for the first time radical-bridged diuranium(iv ) and diuranium(iii ) complexes. Reaction of [UN(SiMe3 )2 3 ] with 2, 2′-bipyrimidine (bpym) resulted in the formation of the bpym-bridged diuranium(iv ) complex [((Me3 Si)2 N)3 U IV 2 (μ-bpym 2− )], 1 . Reduction with 1 equiv. KC8 reduces the complex, affording [K(2.2.2-cryptand)][((Me3 Si)2 N)3 U2 (μ-bpym)], 2, which is best described as a radical-bridged U III –bpym˙ − –U III complex. Further reduction of 1 with 2 equiv. KC8, affords [K(2.2.2-cryptand)]2 [((Me3 Si)2 N)3 U III 2 (μ-bpym 2− )], 3 . Addition of AgBPh4 to complex 1 resulted in the oxidation of the ligand, yielding the radical-bridged complex [((Me3 Si)2 N)3 U IV 2 (μ-bpym˙ − )][BPh4 ], 4 . X-ray crystallography, electrochemistry, susceptibility data, EPR and DFT/CASSCF calculations are in line with their assignments. In complexes 2 and 4 the presence of the radical-bridge leads to slow magnetic relaxation.